Las plumas en los rituales inkas de Tambo Viejo - Valdez, Lidio M. (2025)
The Inka state was well aware that the natural world we live in coexists with an invisible, supernatural world inhabited by divine beings who—from their standpoint—influenced human life. In order to establish and maintain good relations with these beings, the Inkas found it convenient to organise ritual ceremonies and to make various offerings. The gods corresponded to this show of goodwill by sending rains that made good harvests possible. The goods offered as presents were the best available and these included multicoloured bird feathers. This paper presents the archaeological excavations undertaken at the Inka provincial centre of Tambo Viejo, where tropical bird feathers have been found amidst several of the offerings placed inside storehouses. Here we discuss the ritual use of these items throughout the Inka period, and the special significance of their discovery amongst these goods items outside the capital city of Tawantinsuyu.